Effect of different irrigation protocols on the removal of mono and multispecies biofilms, depth of penetration and changes in the dentin surface - Costa, Vanessa Abreu Sanches Marques (2021)
The aim of the present study was to evaluate the antimicrobial action against mono and multispecies biofilms, the chemical changes in dentine surface, by Attenuated Total Reflectance in Fourier Transform Infrared Spectroscopy (ATR-FTIR), microhardness, Picrosirius Red staining and the influence of contact time and activation of irrigants on dentinal penetration by Optical Coherence Tomography (OCT), after submission to different irrigation protocols. Dentine samples from bovine teeth (N=20) were submitted to the irrigation protocols after in vitro induction of monospecies and dual-species biofilms. Live/dead dye and a confocal laser scanning microscope were used to measure the percentage of living cells. The samples for ATRFTIR (N=10) were analyzed before and after the treatments and the proportions of amide III / phosphate and carbonate / phosphate were determined. For the OCT, crosssectional images were obtained from the samples (N=5), before and after the irrigation protocols, and the mean depth of penetration () was obtained. Microhardness (N=12) was measured with Knoop indenter under a 25 g load for 15 seconds, before and after treatments. Samples passed through a histological processing to Sirius Red staining (n=12) after irrigation schemes. Data were statistically compared (P <.05). For the E. faecalis biofilm, the PUI groups had the best antimicrobial action regardless of chemical action (P <.05). Easy Clean worked best with chlorhexidine, regardless of time or NaOCl in longer contact time (P <.05). Against E. faecalis and S. oralis, only Easy Clean with saline solution, regardless of time, did not have an antimicrobial action (P >.05), as well as PUI saline solution, for the biofilm of E. faecalis with C.albicans, and Easy Clean in less agitation time with saline solution (P >.05).The irrigant contact time intensified the dissolution of the dentin collagen reducing the amide III/phosphate ratio when in contact for 30 minutes with NaOCl (P <.05); In the carbonate/phosphate ratio, there were no intergroup differences (P >.05), only intra-group changes in conventional irrigation, PUI and EasyClean treatments with saline solution (P <.05). The diffusion values of irrigants in dentin reveal in the intragroup analysis that, except for conventional irrigation with saline, there was a significant diffusion of irrigants, through the tested protocols (P <.05). In the intergroup analysis, no significant differences were observed (P >.05). Except for the saline group, immersed in 30 minutes, there were no statistically significant differences in relation to their initial microhardness values (P >.05) and there were no intergroup differences (P >.05). All groups showed birefringence for greenish, yellow and red fibers, demonstrating the maturation dynamics of the matrix. The agitation of irrigants by the PUI technique and continuous rotation with Easy clean, as well as the association with the factors of time and chemical action, favors the microbial reduction on the dentin surface among the studied biofilms. The use of NaOCl for prolonged time or with continuous agitation causes greater deproteination of the organic matrix of dentin compared to saline solution. Some carbonate ions are removed in the inorganic phase of the dentine by the saline solution. The agitation and contact time of the sodium hypochlorite, chlorhexidine or saline irrigating solutions and the longer contact time favor the penetration of these irrigants in the root dentin. The irrigation regimes applied in this study are not capable of altering dentinal microhardness. The solutions of chlorhexidine and NaOCl, when in contact with the dentin for a prolonged period, can cause a disorganization in the fibrillar network or modify the morphological structure of the dentin substrate.